Rancang Bangun Sistem Informasi Akreditasi Sekolah - Ida Bagus Ketut Widiartha; Ni Made Puspitayanti; Sri Endang Anjarwani (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2019)
School accreditation is public accountability carried out objectively, fairly, transparently and comprehensively. The instruments used in the school accreditation assessment process refer to the National Education Standards which have eight Standard Points. Since there are many standards and criteria that must be met, the school will difficult to fulfill and measure its performance. This study aims to assist schools in carrying out the performance evaluation process, to meet the standards and criteria that refer to the National Education Standards. In this study a system was developed that can help prepare school accreditation, by providing forms that must be filled in by the school and the system will automatically measure school performance, so that the school can find out its weaknesses to be improved immediately. In its development, the Laravel framework was used with PHP, HTML, and JavaScript as a programming language. The development method used was the waterfall method. System testing in this study uses three testing methods, namely unit testing, black box and MOS (Mean Opinion Score).